Starch Consumption May Modify Antiglycan Antibodies and Fecal Fungal Composition in Patients With Ileo-Anal Pouch. Issue 4 (11th December 2018) - Goren, Idan; Godny, Lihi; Reshef, Leah; Yanai, Henit; Gophna, Uri; Tulchinsky, Hagit; Dotan, Iris
Abstract: Background: Inflammatory bowel diseases (IBDs) are characterized by serologic responses to glycans. Patients with ulcerative colitis (UC) after proctocolectomy with ileo-anal anastomosis (pouch surgery) may develop inflammation (pouchitis) that resembles Crohn's disease (CD). We hypothesized that patients' serologic responses were affected by their consumption of dietary sugars. This study analyzed the correlations between antiglycan antibody expression and dietary sugar consumption in patients with UC pouch and the evolution in antibody levels over time. Methods: Patients were followed prospectively for 2 consecutive visits. The following antiglycan carbohydrate antibodies were detected by enzyme-linked immunosorbent assay: antichitobioside (ACCA), antilaminaribioside (ALCA), antimannobioside (AMCA), and anti– Saccharomyces cerevisiae (ASCA) antibodies. Patients completed a food frequency questionnaire. The fungal community in patients' fecal samples was analyzed by sequencing the internal transcribed spacer 2 (ITS2) region of nuclear ribosomal DNA. Results: We included 75 UC pouch patients aged 45.2 ± 14 years who underwent pouch surgery 9.8 ± 6.7 years previously. Of these patients, 34.7% (n = 26) showed seropositivity for antiglycan antibodies. Starch consumption was significantly higher in patients with positive serologic responses ( P = 0.05). Higher starch consumption was associated with higher AMCA and ACCA titers, which increased by 4.08% (0.8%–7.4%; P = 0.014) and 4.8% (0.7%–9.1%; P = 0.007), respectively, for each 10-g increase of dietary starch. The per-patient change in the relative abundance of Candida albicans in fecal samples correlated positively with changes in starch consumption (Spearman's r = 0.72; P = 0.012). Conclusions: Starch consumption correlated with positive antiglycan serology (ACCA and AMCA), suggesting that increased dietary starch intake may promote a specific immune response in patients with IBD.